2018
DOI: 10.1111/ppl.12736
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq analysis unveils gene regulation of fruit size cooperatively determined by velocity and duration of fruit swelling in peach

Abstract: Fruit swelling determines fruit size and usually occurs in two distinct time periods in peach. However, little is known about the gene regulation of fruit swelling. In this study, measurements of longitudinal and transverse diameters in developing and ripening peach fruits unveiled two periods of fruit swelling: the first swelling ends at approximately 65 days after flower blooming (DAFB) and the second swelling starts at approximately 75 DAFB. Comparisons of diameters sizes and development periods among culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Before the description of SR, the study of peach fruit size was restricted to the combination of RNA-Seq and QTL mapping. These approaches have been successfully used to determine critical genes for anthocyanin biosynthesis, stone adhesion, fleshy melting, and fruit swelling [25,26]. Fruit swelling has been related to fruit growth by linking nine highly transcribed genes, located within the QTLs for peach fruit size [27][28][29][30], to the swelling process [25].…”
Section: Introductionmentioning
confidence: 99%
“…Before the description of SR, the study of peach fruit size was restricted to the combination of RNA-Seq and QTL mapping. These approaches have been successfully used to determine critical genes for anthocyanin biosynthesis, stone adhesion, fleshy melting, and fruit swelling [25,26]. Fruit swelling has been related to fruit growth by linking nine highly transcribed genes, located within the QTLs for peach fruit size [27][28][29][30], to the swelling process [25].…”
Section: Introductionmentioning
confidence: 99%
“…Baixianglu fruit presents a semifreestone melting flesh phenotype, and the fruits of the other ten peach cultivars present a clingstone melting flesh phenotype. Based on the dynamic investigation of fruit development and ripening 71 , the fruits of cv. Xiahui No.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, bHLH was defined as the upstream factor regulating cell expansion-related genes in peaches [13]. In this study, four bHLH genes, bHLH3 To investigate the role of the four bHLH transcription factors (TFs) on the expression of cell expansion-related genes, full-length sequences of the four bHLH genes were amplified and inserted into pSAK277 as effectors.…”
Section: Regulation Of Bhlhs In Cell Expansion-related Genesmentioning
confidence: 99%
“…The distinction between single and double sigmoid patterns is whether a slow-growth period occurs during fruit enlargement. A previous study reported that cooperation between the velocity and duration of fruit swelling determines fruit size [13], which is determined by both cell number and size [14][15][16]. Currently, little is known about the genes that control fruit size, with the exception of genes involved in the cell cycle, cell wall metabolism, cytochrome, and ubiquitin [13,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation